PERSONIFICATION IN KALILA WA DIMNA AND METAPHOR IN 1001 NIGHTS WITHIN ABBASID ERA - Alwasilah, Galang; Rusmana, Dadan; Sakinah, Myrna Nur (CALL, 2023)
This study examined literary works of the Abbasid era, focusing on narratives from 1001 Nights and Kalila Wa Dimna. It tried to contribute to the understanding of Abbasid literature. Through textual analysis and library research, the study explored the cultural and social dimensions of the era. It used a descriptive qualitative method. The findings revealed there were frequent use of personifications and metaphoric existed in both literary works, which enhanced characterization and conveyed moral lessons. The narratives from 1001 Nights and Kalila Wa Dimna provide captivating stories that entertain readers and offer insights into human experiences and wisdom. In conclusion, there were limitations in the reliability of the narratives and the subjective nature of the evaluation.Â Keywords: Abbasid era, 1001 Nights, Kalila Wa Dimna, personification, metaphor